Low Antioxidant Enzyme Levels and Oxidative Stress in Laryngopharyngeal Reflux (LPR) Patients. - Bulut, Fuat; Tetiker, Aylin Türksever; Çelikkol, Aliye; Yılmaz, Ahsen; Ballica, Basak (Journal of Voice, 2023)
Laryngopharyngeal reflux disease (LPR) is a characterized by symptoms different from gastroesophageal reflux disease (GERD). LPR can causes chronic mucosal inflammation which may lead to an increase in cytokine production, and a systemic decrease in antioxidant enzyme levels. Our aim in this study is to evaluate antioxidant enzyme levels in patients with LPR. Reflux Symptom Index (RSI) questionnaire, extraesophageal symptom questionnaire which is included in RSI and Reflux Finding Score (RFS) evaluation with 70° rigid laryngoscope were performed to patients who applied to the otolaryngology clinic with a typical LPR complaint, and 60 patients who had an RSI score above 13 and an RFS score above 7 were included in the study. Thirty people consisting of healthy volunteers were included in the control group. Antioxidant enzyme SOD, GSH-Px and CAT levels were measured in the blood serum of the patients and compared with the control group. Results obtained from biochemical tests were expressed as mean ± SE. Descriptive statistical methods (mean ± standard error) were used for the independent t test for the control and study group. P < 0.05 was considered statistically significant. In the LPR group, 28 (46%) were women, 32 (53%) were men, and age range was 21–60, average age was 36.45 ± 1.147.There was no significant difference between LPR and control group in terms of age, gender and Body Mass Index (BMI). In the LPR group, the lowest score for RSI was 14 and the highest score was 39. The average RSI was 23.67. RFS ranges from 8–22. The mean RFS was 13.50. A highly significant statistical correlation was observed between RSI and total RFS (P < 0.001). There was a significant difference between the antioxidant enzyme levels of the control group and the LPR group. Antioxidant enzyme levels of the control group were SOD 274.10 ± 26.836 U / L, GSH-Px 174.20 ± 20.699 µU / mL and CAT 42.2898 ± 20.699 KU / L. Antioxidant enzyme level results of the LPR group were SOD 147 ± 14.022 U / L (P < 0.01), GSH-Px 88.28 ± 9.113 µU / mL (P < 0.01) and CAT 12.67 ± 0.799 KU / L (P < 0.001). The RSI results ranges from 4 to 39 and the RFS from 8 to 22. Antioxidant enzyme levels demonstrated fairly consistent reliability with individual variables from both RFS and RFS. There was also a highly significant statistical correlation between RSI and RFS. We found that the antioxidant enzymes SOD, GPX and catalase enzyme levels were significantly lower in LPR patients. Treatment modalities to reduce oxidative stress (OS) in LPR should be investigated.